The crime of torture in Islamic law and positive law and international trustees - ناصر يوسف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
However, the reports of international organizations working in the field of human rights confirm the practice of this crime. However, there have been many crimes of torture on different races and sects under the pretext of the exceptional circumstances of decomposition, as stipulated in the charters and others. Of civil and political human rights instruments, whether they are a state of war or threat of war, internal political instability or any other state of emergency. This research contains the concept of torture language and terminology and its meanings and forms and criminalization in Islamic law and the status law and international trustees.